If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying y = 4x + -1q Reorder the terms: y = -1q + 4x Solving y = -1q + 4x Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Simplifying y = -1q + 4x
| -13+q=-40 | | 4(a+b)+6(b+2a)= | | 5.16.15=b | | 9.6m+6=300.5 | | h+2=13 | | -3x-71=103-9x | | 2(4v+9)=98 | | 4q+2q+3=6q-4 | | 6a+(-2c)+(-4a)+c= | | 2x^2-96=x | | 13x+15=13x-15 | | S-3=5s | | 7(7+2l)=3(9l-1) | | 1gh-4gh+7g-8h+h= | | (-3)y+4+5y=(-6) | | 8x+44=4x-12 | | 4x^2+32+5=0 | | 3.5x-8=58.5 | | -x-71=89-11x | | x=3.4+0.2y | | 25c+7c=m | | 8(-2-4)+12=-60 | | 2x^2-x-96=0 | | 0.3x-0.5y=4.2 | | 12x+4+9x+1+27=180 | | x+4*y=12 | | 3x+x+5+2x+1=78 | | 4x-7x+5-1=13 | | (1x^2+4x-13)-(-1x^2+4x-9)=-1x^2-4 | | 3x=y+17-2x | | 3x+8.7=10.5 | | 9y+-4y=6 |